1990
DOI: 10.1088/0954-3899/16/10/015
|View full text |Cite
|
Sign up to set email alerts
|

Search for resonances in the14C+16O reaction

Abstract: Elastic excitation functions have been measured for the ' I C + '€0 colliding system at incident energies from 38-54 MeV in energy steps of 1 MeV. Evidence was found for resonances at Ecm = 18.2, 19.1, 22.9 and 23.8 MeV, to which a Legendre polynomial analysis allowed the assignment of L = 11, 13, 17 and (15)respectively. The data were compared to model predictions: good agreement was found with the group theoretical approach to resonances and, equivalently, with the anharmonic vibrator-rotator model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
2
4
0
Order By: Relevance
“…The changes occur between two valleys, one which remains roughly stationary around 80 ~ and the other which starts near 70 ~ but moves regularly towards smaller angles with increasing energy. 3 where the comparison is with recently published data by Abbondanno et al [5]. At the lowest energy there is only one maximum between the two valleys; at the highest energy there are four.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…The changes occur between two valleys, one which remains roughly stationary around 80 ~ and the other which starts near 70 ~ but moves regularly towards smaller angles with increasing energy. 3 where the comparison is with recently published data by Abbondanno et al [5]. At the lowest energy there is only one maximum between the two valleys; at the highest energy there are four.…”
Section: Resultssupporting
confidence: 74%
“…These distributions evolve in a simple systematic way. [1] (see also [8]) and d from [5] A comparison between two of these elastic angular distributions and those of other authors is shown in Fig. 2) the angular distributions do not change drastically.…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…7). The weak absorption allowed by small NOC's permits the quasimolecular structures to show up experimentally inelastic and quasielastic channels of the C+ C [90 -92], C+ C [92 -94], and C+ 0 [84,95] reactions. Similar calculated results have been obtained for the N induced reactions, this nucleus having a relatively stable configuration with a closed neutron shell and a high-energy first excited state.…”
Section: Resultsmentioning
confidence: 99%
“…From this similarity, Airy minima with orders higher than A3 are likely to exist below E L =115 MeV before the transition into the molecular resonances with the 16 O+ 14 C structure that have been observed in the E c.m. =30 MeV region [34,35].…”
Section: Airy Structure In Elastic 16 O+ 14 C Scatteringmentioning
confidence: 99%